No evidence for a causal link between Helicobacter pylori infection and nonalcoholic fatty liver disease: A bidirectional Mendelian randomization study - Liu, Yuwei; Xu, Hongqin; Zhao, ZiHan; Dong, Yutong; Wang, Xiaomei; Niu, Junqi (Frontiers in Microbiology, 2022)
Although clinical studies have shown the possible relationship between Helicobacter pylori (H. pylori) infection and the development of nonalcoholic fatty liver disease (NAFLD), their causal relationship is still unknown. This bidirectional Mendelian randomization (MR) study aimed to investigate the causal link between H. pylori infection and NAFLD. Two previously reported genetic variants SNPs rs10004195 and rs368433 were used as the instrumental variables (IVs) of H. pylori infection. The genetic variants of NAFLD were extracted from the largest genome-wide association study (GWAS) summary data with 1,483 cases and 17,781 controls. The exposure and outcome data were obtained from the publicly available GWAS dataset. Then, a bidirectional MR was carried out to evaluate the causal relationship between H. pylori infection and NAFLD. In addition, the GWAS data were also collected to explore the causal relationship between H. pylori infection and relevant clinical traits of NAFLD, including triglycerides, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), fasting blood glucose (FBG), and body mass index (BMI). Genetically predicted H. pylori infection showed no association with NAFLD both in FinnGen GWAS (OR, 1.048; 95% CI, 0.778–1.411; value of p = 0.759) and the GWAS conducted by Anstee (OR, 0.775; 95% CI, 0.475–1.265; value of p = 0.308). An inverse MR showed no causal effect of NAFLD on H. pylori infection (OR,0.978;95% CI, 0.909–1.052; value of p = 0.543). No significant associations were observed between H. pylori infection and the levels of triglycerides, LDL-C, HDL-C, or FBG, while H. pylori infection was associated with an increase in BMI. These results indicated that there was no genetic evidence for a causal link between H. pylori and NAFLD, suggesting that the eradication or prevention of H. pylori infection might not benefit NAFLD and vice versa.